Smith54 said:
I understand that 4^(-2) \(\displaystyle \text{not equal to}\) (-4)(-4) = 16 Shouldn't you multiply -2x16 and get -32a^5b^-4 If you can explain why the 16 goes in the denominator, I can understand that once it goes into the denominator the sign changes and the answer is a^5/8b^4
(-2ab^-2)(16a^4b^-2)
-2a^5b^-4/-16
Smith54,
Look at the use of required, and in certain places, suggested, grouping symbols
with some rules of exponents:
[-2ab^(-2)][4a^(-2)b]^(-2) =
[-2ab^(-2)][4^(-2)]{a^[(-2)(-2)]}b^(-2) =
[-2ab^(-2)]{(1/16)(a^4)[b^(-2)]} =
[-2(1/16)]{(a)(a^4)][(b^(-2)][b^(-2)]} =
(-1/8)(a^5)[b^(-4)] =
-a^5/(8b^4)
-------------------------------------------------------------
Here are the steps more or less in Latex:
\(\displaystyle (-2ab^{-2})(4a^{-2}b)^{-2} \ = \\)
\(\displaystyle (-2ab^{-2})\{(4^{-2})[a^{(-2)(-2)}](b^{-2}) \} \ = \\)
\(\displaystyle \bigg(-2ab^{-2}\bigg)\bigg[\frac{1}{16}(a^{4})b^{-2}\bigg] \ = \\)
\(\displaystyle \frac{-1}{8}(a)(a^4)(b^{-2})(b^{-2}) \ = \\)
\(\displaystyle \frac{-1}{8}(a^5)(b^{-4}) \ = \\)
\(\displaystyle \frac{-a^5}{8b^4}\)